Genomic analysis of the first multidrug-resistant ESBL-producing high-risk clonal lineage Klebsiella pneumoniae ST147 isolated from a cat with urinary tract infection - Sakauchi, Victoria T. S.; Haisi, Amanda [UNESP]; Araújo Júnior, João P. [UNESP]; Ferreira Neto, José S.; Heinemann, Marcos B.; Gaeta, Natália C. (Springer Nature, 2024)
Urinary tract infections (UTIs) are pervasive in human and veterinary medicine, notably affecting companion animals. These infections frequently lead to the prescription of antibiotics, contributing to the rise of antimicrobial-resistant bacteria. This escalating concern is underscored by the emergence of a previously undocumented case: a high-risk clone, broad-spectrum cephalosporin-resistant K. pneumoniae ST147 strain, denoted USP-275675, isolated from a cat with UTI. Characterized by a multidrug-resistant (MDR) profile, whole genome sequencing exposed several antimicrobial-resistance genes, notably blaCTX-M-15, blaTEM-1B, blaSHV-11, and blaOXA-1. ST147, recognized as a high-risk clone, has historically disseminated globally and is frequently associated with carbapenemases and extended-spectrum β-lactamases. Notably, the core-genome phylogeny of K. pneumoniae ST147 strains isolated from urine samples revealed a unique aspect of the USP-276575 strain. Unlike its counterparts, it did not cluster with other isolates. However, a broader examination incorporating strains from both human and animal sources unveiled a connection between USP-276575 and a Portuguese strain from chicken meat. Both were part of a larger cluster of ST147 strains spanning various geographic locations and sample types, sharing commonalities such as IncFIB or IncR plasmids. This elucidates the MDR signature inherent in widespread K. pneumoniae ST147 strains carrying these plasmids, highlighting their pivotal role in disseminating antimicrobial resistance (AMR). Finally, discovering the high-risk clone K. pneumoniae ST147 in a domestic feline with a UTI in Brazil highlights the urgent need for thorough AMR surveillance through a One Health approach.
Keywords: Carbapenemases; Cat; Genomic analysis; One health; Surveillance; Urinary tract infection